Safety of older people at home: An integrative literature review - Kivimäki, Taina; Stolt, Minna; Charalambous, Andreas; Suhonen, Riitta A. (My University, 2020)
Aim: The aim of this review was to examine the relevant health literature, to describe safety in the homes of older and older people's perceptions and understanding of their safety at home based on current literature. Background: Safety is a multifaceted, basic need of older people living at home. Many studies are hospital focused and few focus on safety at home. Research on the safety of older people at home appears to be under-researched. Methods: MEDLINE, CINAHL, Scopus and Web of Science databases from the earliest to August 2017 were investigated. The integrative literature review was conducted in December 2017. The full text of the remaining n = 93 papers was then screened for relevance by inclusion and exclusion criteria which reduced the number by 59 to n = 34. Results: Four dimensions of safety at home were discovered, namely physical, social, emotional and mental, and cognitive safety. Safety dimensions had both positive and negative components. Older people's main wish was to be able to live in their own home for as long as possible. Their perceptions of safety at home was categorised as active living, coping at home, managed living and the knowledge of the existence of disease. Conclusions: The safety of older people at home is a worldwide concern. Identification of safety issues can assist in developing measures to help people stay at home for longer as they age. The management of this would need to take account of all four dimensions of safety, in ways that promote ageing at home. Implications for practice: Learning, understanding and developing new strategies about safety affect everyone who visits the home of older people, and stakeholders have an important role to identify safety risks.
Keywords: Content analysis; Home; Integrative review; Older people; Safety